The Current Status of Greenhouse Gas Reporting by Chinese Companies: A Test of Legitimacy Theory - Chu, C.; Chatterjee, Bikram; Brown, Alistair (Emerald Group Publishing Ltd., 2013)
Purpose – The purpose of this paper is to investigate the factors driving greenhouse gas reporting by Chinese companies. Design/methodology/approach – Content analysis of annual reports and corporate social responsibility (CSR) reports for the year 2010 of the top 100 A-share companies listed on Shanghai Stock Exchange was conducted to investigate the extent of greenhouse gas reporting. Multiple regression analysis was performed to determine the factors driving these companies’ greenhouse gas reporting. Findings – It was found that most Chinese companies reported neutral and good news. The results also indicate larger companies operating in an industry which has higher level of carbon dioxide emissions tend to have higher levels of greenhouse gas disclosures, consistent with the expectation of legitimacy theory. However, profitability and overseas listing were not significantly related to greenhouse gas reporting. This is consistent with the findings of previous literature. Finally, contrary to expectations, state-owned companies report less greenhouse gas information than private companies. Originality/value – The paper contributes towards theory development by testing legitimacy theory in the context of greenhouse gas reporting by Chinese companies and contributes to existing literature on greenhouse gas reporting by focussing on the large emerging economy of China. The practical contribution of the paper rests in the area of accounting practice. The results outline the dearth in greenhouse gas reporting by Chinese companies, suggesting there needs to be future development of accounting standards in this area.